Merancang Model Literasi Media Bagi Digital Natives di Kota Magelang sebagai Kota Layak Anak Melalui Child-Led Research - Lintang Citra Cristiani; Jaduk Gilang Pembayun (Journal of Public Administration and Local Governance, 2020)
The development of technology does not go hand in hand with children's ability to respond to information waves. Generation Z children are technically skilled at using media. However, the ability to understand media content, media ethics, and critical understanding is still at a fairly low level. The media literacy movement in Indonesia is understood as digital education, weak in critical thinking, and its various activities are only in the form of top-down socialization. This study aims to find the suitable literacy model for digital natives in Magelang, which is currently predicated as a Kota Layak Anak (KLA) in the Nindya category. In achieving the research objectives, researchers used a qualitative approach with participatory methods that had never been used in previous research with similar themes. This study places children as social actors and leaders in research (child-led research) to produce a media literacy model design with a child's perspective. Children's aspiration data shows that the media literacy model that has been accepted is in the form of one-way socialization so that it does not have much effect on their lives. Children expect a discussion space to convey their opinions on current issues and government policies related to children. In accordance with the aspirations of these children, media literacy based on the journalist community (children-led community) can be used as one of the media literacy models that can be applied in KLA. This model can lead to the fulfillment of the fourth KLA cluster indicators, namely the available creative space that can be used by children. At the same time, this literacy model helps to realize cluster two and also fulfill children's civil rights as an indicator in cluster one.